1997
DOI: 10.1177/074873049701200209
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Melatonin Rhythms in the Goldfish, Carassius auratus

Abstract: Ocular melatonin rhythms in the goldfish were studied and compared to those in the pineal organ and plasma. Under light:dark (LD) of 12 h light:12 h dark, melatonin contents in the eye as well as the pineal organ and plasma exhibited clear day-night changes with higher levels at mid-dark than at mid-light. However, melatonin contents in the eye at mid-light and mid-dark were approximately 100 and 9 times greater than those in the pineal organ, respectively. Day-night changes of ocular melatonin persisted after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…These low expression levels are in agreement with the general acceptance that AANAT-2 is preferentially expressed in the pineal, whereas the most abundant isoform in the retina is the AANAT-1 (Klein, 2007;. Nevertheless, our results indicate that in the goldfish retina an AANAT-2, with parallel rhythmic expression to ocular MEL rhythms (Iigo et al, 1997) could eventually produce MEL, in addition to a possible role on reduction of cytotoxic compounds formation, as suggested (Klein, 2006). Further information on gAANAT-1 is needed to delve into the role of both enzymes in the retina of this species.…”
Section: Daily Rhythmic Expression and Transcriptional Regulationsupporting
confidence: 76%
See 1 more Smart Citation
“…These low expression levels are in agreement with the general acceptance that AANAT-2 is preferentially expressed in the pineal, whereas the most abundant isoform in the retina is the AANAT-1 (Klein, 2007;. Nevertheless, our results indicate that in the goldfish retina an AANAT-2, with parallel rhythmic expression to ocular MEL rhythms (Iigo et al, 1997) could eventually produce MEL, in addition to a possible role on reduction of cytotoxic compounds formation, as suggested (Klein, 2006). Further information on gAANAT-1 is needed to delve into the role of both enzymes in the retina of this species.…”
Section: Daily Rhythmic Expression and Transcriptional Regulationsupporting
confidence: 76%
“…The functional role played by AANAT-2 in these locations, is of great interest and several possibilities, apart from the MEL synthesis, can be suggested, as the reduction of the oxidative formation of aldehydes of serotonin and other arylalkylamines (Bernard et al, 1995;Coon et al, 2002) and/or a detoxification role, as it is considered the original function of this enzyme Klein, 2007). Nevertheless, in addition to the expected Hiomt expression in goldfish pineal and retina, where MEL synthesis is well documented in vivo and in vitro (Iigo et al, 1991;1997), we found positive signals for HIOMT transcripts in gonads and, to a lesser extent, in liver and gut. These are the first results identifying Hiomt transcripts in non photosensitive organs in fish, and accords with previous studies in rat (Stefulj et al, 2001) and quail (Fu et al, 2001).…”
Section: Distribution Of Aanat-2 and Hiomt-2 Mrna In Goldfishmentioning
confidence: 99%
“…The retina shares many chronobiological characteristics with the pineal gland and can be considered a melatoninsynthesising molecular clock in some, but not all, fish species. In the cyprinids zebrafish and goldfish, retinal melatonin rhythms are light sensitive and parallel those of the pineal gland (Cahill 1996, Iigo et al 1997a. However, in rainbow trout (Besseau et al 2006) and European sea bass (Dicentrarchus labrax; Iigo et al 1997b), retinal melatonin production peaks during the daytime.…”
Section: Melatoninmentioning
confidence: 99%
“…As the melatonin concentration in the fish retina is higher than in plasma, e.g. 9-100 times higher in C. auratus (Iigo et al 1997), it may be a signal that dipostomula respond to upon contact with the retina. Whether they can also localize the retina following a concentration gradient of melatonin is difficult to evaluate, as ocular melatonin acts in an autocrine or paracrine manner and seems to accumulate in the eye.…”
Section: Discussionmentioning
confidence: 99%